Nitric Oxide Synthase - Simple Enzyme-Complex Roles 2017
DOI: 10.5772/67816
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nitric Oxide Synthase in the Function of the Central Nervous System under Normal and Infectious Conditions

Abstract: Nitric oxide (NO) was discovered as an endothelium-derived relaxing factor more than two decades ago. Since then, it has been shown to participate in many pathways. NO has been described as a key mediator of different pathways in the central nervous system (CNS) in both healthy and diseased processes. The three isoforms of nitric oxide synthase differ in their activity patterns and expression in different cells. Neuronal nitric oxide synthase (nNOS) is localized in synaptic spines, astrocytes, and the loose co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Next, we checked the production of nitrite as readout for NO production in the peritoneal cavity after treatment with 1 mg/kg dasatinib. NO and superoxide generate antimicrobial molecules called reactive nitrogen species that act together with ROS in damaging cells and microbes ( 46 , 47 ). Our results show that dasatinib increased local nitrite production during CLP, which contributes to bacterial clearance (Figure 7 C).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we checked the production of nitrite as readout for NO production in the peritoneal cavity after treatment with 1 mg/kg dasatinib. NO and superoxide generate antimicrobial molecules called reactive nitrogen species that act together with ROS in damaging cells and microbes ( 46 , 47 ). Our results show that dasatinib increased local nitrite production during CLP, which contributes to bacterial clearance (Figure 7 C).…”
Section: Resultsmentioning
confidence: 99%
“…To explain more, increased NADPH will bring about increased reduction of nitro blue tetrazolium to diformazan (the visible dye) inside the neurons containing NADPH diaphorase which were not NADPH-d + when PPP and, subsequently NADPH concentration was low. Interestingly, NADPH-d + neurons in the hippocampus are demonstrated to release GABA too, indicating that NO acts as a paracrine/retrograde co-transmitter [ 65 ]. If so, loss of these GABAergic neurons could be a cause of disappeared IPSPs following the kainic acid injection, mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Justice et al [ 72 ] showed a similar result in healthy older subjects as time to complete TMT-B was improved by 18% and 14% in response to supplementation with high and low doses of sodium nitrite for 10 weeks, respectively. Potential mechanisms explaining the cognitive effects could include a CR-induced Akt phosphorylation through the insulin-PI3K-Akt signalling pathway [ 73 , 74 ], increased NO production, and potentiation of pre-synaptic neurotransmission [ 75 , 76 ] occurring alongside an enhancement of neurovascular and metabolic coupling [ 77 ].…”
Section: Discussionmentioning
confidence: 99%